HUBUNGAN PARTISIPASI ANGGOTA DENGAN PENERIMAAN SHUDI KOPERASI UNIT DESA KARYA SAWIT DESA BUKIT KRATAI KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Muhammad Hadi Putra; Suarman '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to identify and analyze the relationship between the participation of members of the cooperative with SHU reception at the Village Unit Cooperatives (KUD) Karya Sawit subdistrict Rumbio Kratai Bukit Desa Jaya Kampar regency. This study was conducted from March to May 2016. The subjects were members of the Village Unit Cooperatives (KUD) Karya Sawit subdistrict Rumbio Kratai Bukit Desa Jaya Kampar Regency as many as 48 people. The sample used (sample random sampling). The data used is secondary data, namely data necessary to support the analysis and discussion of members' savings and reception of data SHU. Data analysis techniques in this study is to test Rank Spearman nonparametric statistical methods that are processed through the program SPSS 18 and Microsoft Excel program. The results of this study indicate that the participation of the members has a positive and significant relationship with the reception SHU. The higher the participation of members of the higher SHU received by members. Keywords: Participation of members, SHU Acceptance